Association between tracheostomy timing and outcomes for older critically ill COVID-19 patients: prospective observational study in European intensive care units. (March 2022) - Polok, Kamil; Fronczek, Jakub; van Heerden, Peter Vernon; Flaatten, Hans; Guidet, Bertrand; De Lange, Dylan W.; Fjølner, Jesper; Leaver, Susannah; Beil, Michael; Sviri, Sigal; Bruno, Raphael Romano; Wernly, Bernhard; et al.
Abstract: Background: Tracheostomy is performed in patients expected to require prolonged mechanical ventilation, but to date optimal timing of tracheostomy has not been established. The evidence concerning tracheostomy in COVID-19 patients is particularly scarce. We aimed to describe the relationship between early tracheostomy (≤10 days since intubation) and outcomes for patients with COVID-19. Methods: This was a prospective cohort study performed in 152 centres across 16 European countries from February to December 2020. We included patients aged ≥70 yr with confirmed COVID-19 infection admitted to an intensive care unit, requiring invasive mechanical ventilation. Multivariable analyses were performed to evaluate the association between early tracheostomy and clinical outcomes including 3-month mortality, intensive care length of stay, and duration of mechanical ventilation. Results: The final analysis included 1740 patients with a mean age of 74 yr. Tracheostomy was performed in 461 (26.5%) patients. The tracheostomy rate varied across countries, from 8.3% to 52.9%. Early tracheostomy was performed in 135 (29.3%) patients. There was no difference in 3-month mortality between early and late tracheostomy in either our primary analysis (hazard ratio [HR]=0.96; 95% confidence interval [CI], 0.70–1.33) or a secondary landmark analysis (HR=0.78; 95% CI, 0.57–1.06). Conclusions: There is a wide variation across Europe in the timing of tracheostomy for critically ill patients with COVID-19. However, we found no evidence that early tracheostomy is associated with any effect on survival amongst older critically ill patients with COVID-19. Clinical Trial registration: ClinicalTrials.gov NCT 04321265.